Improved agronomic practices for enhanced productivity of small millets - Swarna, R; Deepika, C; Amasiddha, B; Srividhya, S (Indian Farming, 2023)
Small millets termed as nutri-cereals hold great promise for food and nutrition security amid burgeoning population and climate change. Nutritionally, these are superior to the cereals in terms of protein, minerals and amino acids. In India, small millets are largely cultivated under resource constraint conditions resulting in low crop productivity. Thus adoption of improved agronomic practices is the key to increase their productivity and project them as golden crops of the future.